Public Internal Control in the European Union - Faituša, Ivita (My University, 2015)
Public internal control differs from country to country as it has to fit into the respective overall governance arrangements with the government and the supreme audit institution as well as the accountability arrangements that exist between stakeholders. The aim of this research is to find out common and different internal control elements in twelve European Union (EU-12) countries. The tasks of this research are: to analyse revenue indicators in the EU countries, to analyse internal control systems in the EU countries, to make conclusions and to make proposals for further research tasks about the internal control of the administration of Latvia and improvements of the internal audit systems. The methods of this research are economic analysis (monograph) method and graphic method. The main results from this research – not all of the countries interpret the concept of internal control in the same way – some countries have special independent internal control institutions, in some countries, decentralised system of internal control is embedded and forms an integrated part of the administration. More and more countries also require top managers to apply systems for managing or mitigation of the risk of not achieving set objectives. Almost all of the EU member states have established internal audit function, but do not cover all systems of public administration.
Keywords: internal control; audit; public administration